The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1111/j.1600-0528.1992.tb01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in restorative treatment decisions: application of Receiver Operating Characteristic curve (ROC) analysis

Abstract: It has been evident for many years that dentists, when planning treatment for patients, do not act in a standard manner, and previous research has shown there to be wide variations in treatment planning amongst groups of dentists. Signal detection theory and Receiver Operating Characteristic (ROC) analysis allows measurement of an observer's ability to detect a lesion, while at the same time allowing examination of how a lesion, once perceived, is judged to be in need of treatment. An ROC curve is constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…The method is equivalent to repeatedly asking dentists to make a simple dichotomous decision whilst altering their attitudes towards interventive treatment (Hanley & McNeil 1982). The area beneath an ROC curve therefore estimates the probability that a radiographically evident lesion is treated as `more abnormal' by a dentist (or group of dentists) than a radiograph of a sound tooth (Kay & Knill‐Jones 1992). The areas under the ROC curves for each dentist and for all dentists in each of the three groups were derived using a computer program (Centor 1985).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method is equivalent to repeatedly asking dentists to make a simple dichotomous decision whilst altering their attitudes towards interventive treatment (Hanley & McNeil 1982). The area beneath an ROC curve therefore estimates the probability that a radiographically evident lesion is treated as `more abnormal' by a dentist (or group of dentists) than a radiograph of a sound tooth (Kay & Knill‐Jones 1992). The areas under the ROC curves for each dentist and for all dentists in each of the three groups were derived using a computer program (Centor 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown considerable clinical variability in dental restorative treatment thresholds and decisions (Mileman et al 1982; Elderton & Nuttall 1983), and a previous study by Kay et al (1992) indicated that the key to achieving `good' clinical decisions lies in educating practitioners to understand the trade‐offs between false negative and false positive errors. Another study which focused on the reduction of clinical variability suggested that, if a clinician understands the principles underlying receiver operating characteristic curve analysis, his/her ability to make decisions consistent with his/her own attitudes to treatment might be improved (Hanley & McNeil 1982; Kay & Knill‐Jones 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The investigators had to indicate on a 6-point confidence rating scale the certainty of their decision: 0 = definitely not, 1 = probably not, 2 = possibly not, 3 = possibly, 4 = probably, 5 = definitely. The characteristics of the imaginary patient were briefly described in accordance with a previously published patient's profile: 20-year-old patient, general medical anamnesis inconspicuous, average caries experience and oral hygiene level, readiness to observe regular recall dates over years to come [Kay and Knill Jones, 1992]. No information was given on lesion prevalence.…”
Section: Data Collectionmentioning
confidence: 99%
“…64 The consistency within individual practitioners’ treatment approaches across primary occlusal caries, primary proximal caries, and secondary caries suggests that diagnostic and treatment differences across practitioners for specific restorations may reflect fundamental differences in dentists’ approaches to similar clinical findings. 16173 The lack of agreement over time will result in a specific patient receiving additional restorative treatment. Some of the additional treatment may be to teeth that will invariably require treatment, however, some will be to teeth that may remain stable over time, particularly in low caries risk populations.…”
Section: Discussionmentioning
confidence: 99%